Strategi Komunikasi Politik Rohidin Mersyah sebagai Calon Petahana Pilkada 2020 Provinsi Bengkulu - Ahmad Yozi Alhidayah (Universitas Baturaja, 2020)
The Political Year 2020 has begun, and Bengkulu Province will not directly elect the Governor and Deputy Governor for the Period of 2021-2026. Prospective Candidates have begun to be shown to the public from the start, known figures and new images will participate in coloring the long process of this democratic party. Rohidin Mersyah, who currently needs a Governor from 2016-2021. The communication strategy has been carried out by establishing communication to the Regions by conducting family gatherings. Social media also plays an important role in the Communication Strategy that is built. Community leaders also have a stake in supporting the strategy. The results of the study explain the strategy that has been expected to influence voters in making choices that do not need the attention of the respondents, seen from the media used to be more millennial consumption.